ChemInform Abstract: Computational Studies on Cinchona Alkaloid‐Catalyzed Asymmetric Organic Reactions. Issue 33 (27th July 2016) - Tanriver, Gamze; Dedeoglu, Burcu; Catak, Saron; Aviyente, Viktorya
Abstract: Review: 75 refs.